(untitled) (Andamios, Revista de Investigación Social, 2014)
The paper proposes a philosophical approach to the city thought through the Marxian concept of phantasmagoria. First I argue an archeological argument about the critical discourse of the philosophy and then a genealogical approach to the political. The paper argues that the city of late capitalism is the city of the phantasmagoria. As a conclusion, I argue that the city of the twentieth Century is the city of biopolitical security.